Stainless steel welded structure and method for manufacturing the same
The stainless steel welded structure addresses corrosion and toughness issues by using laser welding with controlled oxide film thickness and distribution, ensuring a black tone and enhanced resistance.
Patent Information
- Application Number
- JP2023113236
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
AI Technical Summary
Existing stainless steel welded structures with a black oxide film face issues of reduced corrosion resistance and toughness at the weld metal part due to oxide film entrapment and localized oxides, which are not addressed by existing methods.
A stainless steel welded structure is formed using laser welding with specific composition and oxide film parameters, including a predetermined thickness and carrier density, along with controlled area ratio and oxide distribution to enhance corrosion resistance and toughness.
The method results in a stainless steel welded structure with a black tone and improved corrosion resistance and toughness, suitable for applications requiring these properties.
Smart Images

Figure 2025010923000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a stainless steel welded structure and a method for manufacturing the same. [Background technology]
[0002] Stainless steel is a material with excellent corrosion resistance, and taking advantage of its shiny silver-white surface, it is used in various products such as interior and exterior building materials, exhaust system parts, etc. In order to enhance the design of stainless steel, it is often given a color tone, typically black, using methods such as chemical coloring, painting, and oxidation treatment.
[0003] For example, the method of forming an oxide film on the surface of stainless steel (material) by oxidation treatment methods such as those described in Patent Documents 1 and 2 allows for continuous treatment using continuous annealing equipment, which is a general-purpose manufacturing process for stainless steel, and has higher productivity than other treatments such as chemical coloring. The oxide film formed by this oxidation treatment method has good corrosion resistance because a layer mainly made of protective Cr oxide is formed. Patent Documents 3 to 6 also propose techniques for forming a black oxide film with good corrosion resistance by controlling the composition of the stainless steel material and the conditions during oxidation treatment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-178392 A [Patent Document 2] JP 2018-135591 A [Patent Document 3] JP 2022-103735 A [Patent Document 4] JP 2022-103732 A [Patent Document 5] Japanese Patent Application Publication No. 11-061376 [Patent Document 6] Japanese Patent Application Publication No. 10-330904 Summary of the Invention [Problem to be solved by the invention]
[0005] Stainless steel material with a black oxide film is processed into a predetermined shape, and then a part of the processed material is welded to produce various products (stainless steel welded structures). At this time, the oxide film on the surface is rolled up into the weld metal part and solidifies. Since no oxide film is formed on the surface of the weld metal part, the corrosion resistance of the weld metal part is likely to decrease. In addition, if large oxides resulting from the oxide film are present locally without being dispersed in the weld metal part, the toughness of the weld metal part is also likely to decrease. Patent Documents 1 to 6 do not recognize the problem that when welding is performed on a stainless steel material having a black oxide film, the corrosion resistance and toughness of the welded metal part decreases.
[0006] The present invention has been made to solve the above-mentioned problems, and has an object to provide a stainless steel welded structure having a black color tone and excellent corrosion resistance and toughness of the weld metal part, and a method for manufacturing the same. [Means for solving the problem]
[0007] As a result of intensive research to solve the above problems, the inventors have found that the corrosion resistance and toughness of a welded metal part can be improved by using a stainless steel material having a specified composition on which an oxide film having a specified thickness and carrier density is formed, and performing laser welding under specific conditions. They also found that the welded metal part formed by such a method has an area ratio of a surface area with a diameter of 20 mm and an oxide number density within a specified range. The present invention has been completed against this background.
[0008] That is, the present invention is a stainless steel welded structure having a base material and a weld metal part, The base material is a stainless steel material having a material portion and an oxide film formed on the material portion, the material portion has a composition, on a mass basis, of C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities; The oxide film has a thickness of 300 to 1000 nm and a carrier density of 2.0 × 10 20 pieces / cm 3 is as follows: The weld metal part has a density of oxide particles having a major axis of 1 μm or more of 5 particles / mm 2 is as follows: This is a stainless steel welded structure, in which the area ratio of the weld metal portion to a surface area having a diameter of 20 mm centered on the weld metal portion is 20.0% or less.
[0009] The present invention also provides a method for manufacturing a semiconductor device comprising the steps of: a material part; and an oxide film formed on the material part, the material part containing, by mass, C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities; and the oxide film having a thickness of 300 to 1000 nm and a carrier density of 2.0×10 20 pieces / cm 3 A method for manufacturing a stainless steel welded structure by laser welding stainless steel materials that are as follows: Laser welding is performed with the irradiation energy [kJ / mm] relative to the thickness [mm] of the stainless steel material. 2 The present invention relates to a method for producing a stainless steel welded structure, in which the value of [kJ / mm] is 10.0 to 30.0 kJ / mm. Effect of the Invention
[0010] According to the present invention, it is possible to provide a stainless steel welded structure which has a black color tone and excellent corrosion resistance and toughness of a welded metal part, and a method for manufacturing the same. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic enlarged partial cross-sectional view of a stainless steel welded structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.
[0013] A stainless steel welded structure according to an embodiment of the present invention has a base material and a weld metal part. This stainless steel welded structure is manufactured by laser welding a stainless steel material as a base material.
[0014] FIG. 1 shows a schematic enlarged partial cross-sectional view of a stainless steel welded structure. 1, the stainless steel welded structure (100) includes a base material (10) and a welded metal portion (30). The stainless steel welded structure (100) further includes a heat-affected zone (20) between the base material (10) and the welded metal portion (30). The base material (10) is a stainless steel material having a material portion (11) and an oxide film (12) formed on the material portion (11).
[0015] In this specification, the term "base material" refers to a portion that is not affected by welding. The term "heat-affected zone" refers to a portion that is not melted by welding but is affected by heat (also called HAZ). The term "weld metal zone" refers to a portion that melts and resolidifies due to welding. In addition, in this specification, the term "stainless steel material" refers to a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate shape (including a strip shape), a rod shape, a tube shape, and the like. In addition, the material may be various shaped steels having a cross-sectional shape such as a T shape or an I shape.
[0016] The material portion has a composition containing C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities. In this specification, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of stainless steel materials, and are acceptable within a range that does not adversely affect the present invention. For example, impurities include unavoidable impurities. An example of an impurity is O. With regard to the content of each element, "xx% or less" means that the content is xx% or less, but includes an amount exceeding 0% (particularly, exceeding the impurity level).
[0017] If necessary, the material part may further contain at least one selected from Nb: 0.50% or less, Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less. Each component will be described in detail below.
[0018] (C: 0.100% or less) C is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect) and workability. However, if the C content is too high, the workability and intergranular corrosion resistance of the stainless steel material will decrease. Therefore, the upper limit of the C content is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the C content is not particularly limited, but excessively reducing the C content leads to an increase in refining costs. Therefore, the lower limit of the C content is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%.
[0019] (Si:1.00% or less) Silicon is an element that improves the oxidation resistance of stainless steel materials. However, if the content of silicon is too high, the workability and the toughness of the welded joint are reduced. Therefore, the upper limit of the content of silicon is 1.00%, preferably 0.90%, and more preferably 0.80%. On the other hand, the lower limit of the content of silicon is not particularly limited, but is preferably 0.005%, more preferably 0.01%, and even more preferably 0.015% from the viewpoint of obtaining the effect of silicon.
[0020] (Mn: 0.05 to 1.00%) Mn is an element that is effective in ensuring the color tone of the oxide film (blackened film after heat treatment). In particular, Mn gives a black color tone by forming a complex oxide with Cr. However, if the Mn content is too high, MnS, which is the starting point of corrosion, is easily generated and the ferrite phase is destabilized. Therefore, the upper limit of the Mn content is 1.00%, preferably 0.90%, and more preferably 0.80%. On the other hand, if the Mn content is too low, the above effects may not be sufficiently obtained. Therefore, the lower limit of the Mn content is 0.05%, preferably 0.055%, and more preferably 0.06%.
[0021] (Ni: 1.00% or less) Ni is an element effective for improving the corrosion resistance and weld toughness of stainless steel materials. However, if the Ni content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Ni content is 1.00%, preferably 0.90%, and more preferably 0.80%. On the other hand, the lower limit of the Ni content is not particularly limited, but is preferably 0.005%, and more preferably 0.01%, from the viewpoint of obtaining the above-mentioned effects.
[0022] (P:0.100% or less) P is an element that affects the properties of stainless steel materials, such as weldability and workability. If the P content is too high, the above properties may be degraded. Therefore, the upper limit of the P content is 0.100%, preferably 0.080%, and more preferably 0.060%. On the other hand, the lower limit of the P content is not particularly limited, but an excessively low P content leads to an increase in refining costs. Therefore, the lower limit of the P content is preferably 0.001%, and more preferably 0.005%.
[0023] (S:0.100% or less) S is an element that generates MnS, which is a corrosion starting point, and affects the properties of stainless steel materials, such as the toughness of welded parts. If the S content is too high, the above properties may be deteriorated. Therefore, the upper limit of the S content is 0.100%, preferably 0.080%, and more preferably 0.060%. On the other hand, the lower limit of the S content is not particularly limited, but excessively reducing the S content leads to an increase in refining costs. Therefore, the lower limit of the S content is preferably 0.0001%, and more preferably 0.0002%.
[0024] (Cr:16.00~25.00%) Cr is an element that is effective in improving the corrosion resistance of stainless steel materials and forming a uniform oxide film. Cr is also an element that is effective in ensuring the color tone of the oxide film (blackened film after heat treatment). However, if the Cr content is too high, the manufacturing cost increases. Therefore, the upper limit of the Cr content is 25.00%, preferably 24.00%, and more preferably 23.00%. On the other hand, if the Cr content is too low, the above effects cannot be sufficiently obtained. Therefore, the lower limit of the Cr content is 16.00%, preferably 16.50%, and more preferably 17.00%.
[0025] (N:0.100% or less) N is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect) and workability. However, if the N content is too high, the intergranular corrosion resistance and workability of the stainless steel material will decrease. In addition, if the N content is high, TiN will easily precipitate, the amount of solid-solubilized Ti in the steel will decrease, and the formation of a blackened film after heat treatment will be inhibited. In addition, the formed nitrides are likely to become the starting point of corrosion, reducing the corrosion resistance. Therefore, the upper limit of the N content is 0.100%, preferably 0.095%, and more preferably 0.090%. On the other hand, the lower limit of the N content is not particularly limited, but an excessively low N content will lead to an increase in refining costs. Therefore, the lower limit of the N content is preferably 0.001%, and more preferably 0.003%.
[0026] (Ti: 0.08~0.50%) Ti is an element that affects the intergranular corrosion resistance (sensitization suppression effect) of stainless steel materials. In addition, Ti is also an element that is effective in ensuring the color tone of the oxide film (blackened film after heat treatment). In particular, Ti gives a black color tone by forming a composite oxide with Cr, and can also suppress peeling of the oxide film by forming Ti oxide (TiO2) on the surface. However, if the Ti content is too high, the workability and surface quality of the stainless steel material are reduced. Therefore, the upper limit of the Ti content is 0.50%, preferably 0.45%, and more preferably 0.40%. Also, if the Ti content is too low, the above-mentioned effects cannot be sufficiently obtained. Therefore, the lower limit of the Ti content is 0.08%, preferably 0.085%, and more preferably 0.09%.
[0027] (Cu:1.00% or less) Cu is an element effective for improving the corrosion resistance of stainless steel materials. However, if the Cu content is too high, the ferrite phase becomes unstable and the manufacturing cost increases. Therefore, the upper limit of the Cu content is 1.00%, preferably 0.90%, and more preferably 0.80%. On the other hand, the lower limit of the Cu content is not particularly limited, but is preferably 0.005%, and more preferably 0.01%.
[0028] (Mo: 2.00% or less) Mo is an element effective for improving the corrosion resistance and oxidation resistance of stainless steel materials. However, if the Mo content is too high, it leads to a decrease in the workability of the stainless steel material and an increase in the manufacturing cost. Therefore, the upper limit of the Mo content is 2.00%, preferably 1.95%, and more preferably 1.90%. On the other hand, the lower limit of the Mo content is not particularly limited, but is preferably 0.001%, and more preferably 0.01%.
[0029] (Nb:0.50% or less) Nb is an element that affects the properties of stainless steel materials, such as intergranular corrosion resistance (sensitization suppression effect). However, if the Nb content is too high, the workability of the stainless steel material decreases. Therefore, the upper limit of the Nb content is 0.50%, preferably 0.45%, and more preferably 0.40%. On the other hand, the lower limit of the Nb content is not particularly limited, but is preferably 0.005%, and more preferably 0.01%.
[0030] (Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less) Al, Zr, Co, V and W are elements effective for improving the oxidation resistance of stainless steel materials. However, if the content of Al, Zr, Co, V and W is too high, the workability and toughness of the stainless steel material will decrease, and the manufacturing cost will increase. Therefore, the upper limit of the content of Al, Zr, Co, V and W is 1.00%, preferably 0.95%, and more preferably 0.90%. On the other hand, the lower limit of the content of Al, Zr, Co, V and W is not particularly limited, but is preferably 0.0001%, more preferably 0.001%, and even more preferably 0.01%.
[0031] (REM: 0.100% or less, Ca: 0.100% or less) REM and Ca are elements effective for improving the oxidation resistance of stainless steel materials. However, if the REM and Ca contents are too high, it leads to an increase in the manufacturing cost of stainless steel materials. Therefore, the upper limit of the REM and Ca contents is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the REM and Ca contents is not particularly limited, but is preferably 0.0001%, more preferably 0.0003%, and even more preferably 0.001%. In addition, REM is a general term for Sc, Y, and lanthanoids, a total of 17 elements, and refers to rare earth metals. Specifically, La, Ce, Nd, etc. can be mentioned, and one of these can be contained alone or two or more can be combined. When two or more rare earth elements are contained, the content of the REM refers to the total content of these rare earth elements.
[0032] (Sn:0.100% or less) Sn is an element effective for improving the corrosion resistance of stainless steel materials. However, if the Sn content is too high, Sn segregates and manufacturability decreases. Therefore, the upper limit of the Sn content is 0.100%, preferably 0.090%, and more preferably 0.080%. On the other hand, the lower limit of the Sn content is not particularly limited, but is preferably 0.001%, and more preferably 0.002%.
[0033] (B:0.0100% or less) B is an element effective for improving the secondary workability of stainless steel materials. However, if the B content is too high, the fatigue strength of the stainless steel material decreases. Therefore, the upper limit of the B content is 0.0100%, preferably 0.0090%, and more preferably 0.0080%. On the other hand, the lower limit of the B content is not particularly limited, but is preferably 0.0001%, and more preferably 0.0003%.
[0034] The metal structure of the material portion is ferritic. In this specification, "ferritic" means that the metal structure at room temperature is mainly in the ferritic phase.
[0035] Next, the characteristics of the oxide film formed on the material portion will be described. The oxide film has the function of imparting corrosion resistance and a black color tone to the stainless steel material. The oxide film has a Cr2O3 inner layer and may have a Mn-Cr oxide layer on the outermost surface.
[0036] The Cr2O3 inner layer is the layer on the material side of the oxide film, and has the function of ensuring the barrier properties of the oxide film (its ability to protect the material). The Mn-Cr oxide layer is the surface layer of the oxide film. It is a layer composed of a composite oxide of Mn and Cr (Mn-Cr spinel oxide) and has the function of imparting a black color tone to the oxide film.
[0037] The oxide film has a thickness of 300 to 1000 nm and a carrier density of 2.0 × 10 20 pieces / cm 3 The oxide film is L * a * b * Lightness index L in color system * is 50.0 or less, Chromathetics Index a * and b * It is preferable that the difference is within ±5.00. The reasons for these limitations will be explained.
[0038] (Thickness: 300~1000nm) The thickness of the oxide film (the entire oxide film including the Cr2O3 inner layer and the Mn-Cr oxide layer) affects the color tone. From the viewpoint of imparting a desired black color tone, the lower limit of the oxide film thickness is 300 nm, preferably 310 nm, and more preferably 320 nm. On the other hand, if the oxide film is too thick, it is more likely to crack or peel off during processing of the stainless steel material. Therefore, the upper limit of the oxide film thickness is 1000 nm, preferably 950 nm, and more preferably 900 nm. In this specification, the thickness of the oxide film is defined as the depth from the surface to the position where O (oxygen) is 1 / 4 of the maximum value in the component concentration profile in the depth direction obtained by glow discharge optical emission spectroscopy (GD-OES). The concentration of the element can be determined by glow discharge optical emission spectroscopy (GD-OES).
[0039] (Carrier density: 2.0×10 20 pieces / cm 3 below) Metal corrosion progresses as a result of the pairing of metal dissolution (anodic reaction) and oxygen reduction (cathodic reaction) around the metal dissolution area. This is because electrical neutrality is maintained by consuming electrons generated in the anodic reaction in the cathodic reaction. Therefore, if the cathodic reaction in stainless steel materials can be suppressed, the anodic reaction (metal dissolution) can also be suppressed. The cathodic reaction occurs in an environment where water is present, when electrons generated in the anodic reaction move inside the metal and react with oxygen dissolved in the water on the surface. Therefore, the cathodic reaction can be suppressed by covering the surface of the metal with an insulating material that makes it difficult for electrons to move. However, an oxide film mainly composed of Cr2O3 does not have sufficient insulation because structural defects (e.g., oxygen vacancies or metals with a different valence from Cr) act as carriers that carry the electrons, and the cathodic reaction cannot be sufficiently suppressed. Therefore, in order to sufficiently suppress the cathodic reaction in stainless steel materials, it is important to control the carrier density of the oxide film.
[0040] For the above reasons, the upper limit of the carrier density of the oxide film is 2.0×10 20 pieces / cm 3 , preferably 1.0 x 10 20 pieces / cm 3 In addition, by setting the upper limit of the carrier density of the oxide film as described above, corrosion is less likely to occur even if the material is partially exposed during processing. On the other hand, the lower limit of the carrier density of the oxide film is not particularly limited because the smaller the lower limit, the greater the effect of suppressing the cathodic reaction. Generally, however, it is set to 1.0×10 14 pieces / cm 3 , preferably 1.0 x 10 15 pieces / cm 3 It is. In this specification, the carrier density of the oxide film can be measured by electrochemical impedance measurement.
[0041] (Lightness index L * : 50.0 or less, Chromathetics index a * and b * : within ±5.00) The oxide film is L * a * b * Lightness index L in color system * is 50.0 or less, Chromathetics Index a * and b * is within ±5.00. * , Chromathetics Index a * and b * Within the above range, it can be said that a desired black tone is obtained. Here, in this specification, "brightness index L * " and "Chromathetics Index a * and b * " can be measured in accordance with JIS Z8722:2009.
[0042] Next, the characteristics of the weld metal part will be described. The weld metal part has an oxide density of 5 / mm2 with a major axis of 1 μm or more. 2 The following is the result. Oxides with a major axis of 1 μm or more contained in the weld metal are mainly due to the oxide film that was caught in the weld metal during welding. If these oxides are not sufficiently dispersed on the surface or inside of the weld metal and exist locally, the toughness of the weld metal is likely to decrease. If the number density of oxides with a major axis of 1 μm or more is 5 particles / mm 2 If the oxides are less than 1 μm in diameter, the oxides can be considered to be sufficiently dispersed on the surface and inside of the weld metal, and the toughness of the weld metal is improved. From the viewpoint of stably improving this effect, the number density of oxides with a major axis of 1 μm or more is set to 4 particles / mm 2 It is preferable that the number of particles is less than 3 / mm. 2 It is more preferable that: Here, in this specification, the number density of oxides having a major axis of 1 μm or more can be obtained as follows. First, the surface of a weld metal part that has been ground and smoothed is measured with an FE-SEM (SU-5000 manufactured by Hitachi High-Tech Corporation) to measure the number of oxides having a major axis of 1 μm or more. 2The range is photographed in 20 fields of view, and the oxides and inclusions are identified through image analysis. Next, the composition of the oxides and inclusions is analyzed by EDX, and oxides with a major axis of 1 μm or more are identified and their number is calculated. The number of oxides with a major axis of 1 μm or more is then calculated based on the observation area (mm 2 ) to obtain the number density (pieces / mm 2 ) can be obtained.
[0043] The area ratio of the weld metal part to the surface area of a 20 mm diameter centered on the weld metal part is 20.0% or less. When the material (stainless steel material) melts, the oxide film on the surface of the weld metal part is rolled up into the material part, resulting in a state in which a part of the material part is exposed. Therefore, the wider the area of the exposed material part (welded metal part), the smaller the effect of suppressing the cathodic reaction becomes, and the lower the corrosion resistance becomes. Therefore, by controlling the area ratio of the weld metal part to 20.0% or less of the surface area of a 20 mm diameter centered on the weld metal part, the effect of suppressing the cathodic reaction can be ensured and the corrosion resistance can be improved. From the viewpoint of stably ensuring this effect, the area ratio of the weld metal part is preferably 19.5% or less, and more preferably 19.0% or less. Here, the area ratio of the weld metal part to a surface region having a diameter of 20 mm centered on the weld metal part can be found as follows. First, the area around the weld metal part is photographed with an optical microscope. Next, the surface region having a diameter of 20 mm centered on the weld metal part is observed, and the weld metal part is distinguished from other parts (heat-affected zone and base metal) by binarization using differences in brightness. Then, the area of the weld metal part is divided by the observation region (surface region having a diameter of 20 mm) and multiplied by 100 to find the area ratio (%) of the weld metal part to a surface region having a diameter of 20 mm centered on the weld metal part.
[0044] The stainless steel welded structure according to the embodiment of the present invention can be manufactured by laser welding together stainless steel materials having the above-mentioned characteristics. That is, the stainless steel welded structure according to the embodiment of the present invention has a base material and an oxide film formed on the base material, the base material contains C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities, and the oxide film has a thickness of 300 to 1000 nm and a carrier density of 2.0 × 10 20 pieces / cm 3 This is performed by laser welding together stainless steel materials that satisfy the following conditions. The stainless steel material material may further contain at least one selected from Nb: 0.50% or less, Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
[0045] The method for producing the stainless steel material used in laser welding is not particularly limited as long as it is a method capable of producing the stainless steel material having the above-mentioned characteristics. For example, the stainless steel material can be produced by using a rolled material having the above-mentioned composition as a raw material and heat treating the rolled material under predetermined conditions.
[0046] The heat treatment of the rolled material is carried out at a temperature of 800°C or higher for 1 minute or longer in an atmosphere in which the O2 concentration is 2 to 20 volume %, the water vapor concentration is 20 volume % or less, and the value represented by the following formula (1) is 15 to 30. 2 × O2 concentration + water vapor concentration (1) By carrying out heat treatment under such conditions, it is possible to form a black oxide film that is difficult to peel off during processing, and it is also possible to improve the corrosion resistance of the stainless steel material.
[0047] If the O2 concentration exceeds 20% by volume, the Cr diffusion in the material slows down and the Cr concentration in the surface layer of the material decreases, making it difficult to form an oxide film with the desired properties. On the other hand, if the O2 concentration is less than 2% by volume, it becomes difficult to form an oxide film with a predetermined thickness. From the viewpoint of stably forming an oxide film with the desired properties and thickness, the O2 concentration is preferably 2 to 18% by volume, and more preferably 2 to 15% by volume. If the water vapor concentration exceeds 20% by volume, the Cr concentration at the interface between the material part and the oxide film becomes high, and the desired corrosion resistance cannot be obtained. From the viewpoint of stably reducing the Cr concentration at the interface between the material part and the oxide film, the water vapor concentration is preferably 18% by volume or less, and more preferably 16% by volume or less.
[0048] If the value represented by formula (1) is outside the range of 15 to 30, the oxidation rate cannot be appropriately controlled, and it becomes difficult to form an oxide film having the desired properties and thickness. From the viewpoint of stably controlling the oxidation rate, the value represented by formula (1) is preferably 16 to 28, and more preferably 18 to 25.
[0049] If the heat treatment temperature is less than 800° C. and the heat treatment time is less than 1 minute, the oxide film will not grow sufficiently and an oxide film of the desired thickness will not be formed. The heat treatment temperature is preferably 900 to 1200°C, and more preferably 950 to 1180°C, from the viewpoint of stably forming an oxide film having the desired characteristics and thickness. Moreover, from the viewpoint of stably forming an oxide film having the desired characteristics and thickness, the heat treatment time is preferably 2 to 500 minutes, and more preferably 2 to 100 minutes.
[0050] Stainless steel materials (especially ferritic stainless steel materials) manufactured as described above have high thermal conductivity. Therefore, if arc welding such as TIG welding is used, the amount of heat input must be excessive, the range of the welded metal part becomes wide, and the corrosion resistance of the welded metal part is likely to decrease. For this reason, laser welding is used as the welding method. By using laser welding, the range of the welded metal part can be narrowed, so that the area ratio of the welded metal part in the surface area with a diameter of 20 mm centered on the welded metal part can be controlled to 20.0% or less.
[0051] Laser welding is performed using the following formula: 2
[0033] is 10.0 to 30.0 kJ / mm, preferably 12.0 to 30.0 kJ / mm, and more preferably 15.0 to 30.0 kJ / mm. By performing laser welding under such conditions, convection occurs when the weld metal part melts, making it easier to disperse oxides mainly originating from the oxide film on the surface and inside of the weld metal part. Therefore, the number density of oxides with a major axis of 1 μm or more is set to 5 / mm 2 The following control is possible:
[0052] Irradiation energy [kJ / mm 2 ] can be controlled by adjusting the laser output, focal diameter, and scanning speed. Specifically, the irradiation energy [kJ / mm 2 ] is expressed by the following equation (2). Irradiation energy [kJ / mm 2 ]=Power density [kW / mm 2 ] × Irradiation time [s] ···(2) In equation (2), the power density [kW / mm 2 ] is expressed by the following formula (3), and irradiation time [s] is expressed by the following formula (4). Power density [kW / mm 2 ]=Power [kW] / ((Focal diameter [mm] / 2) 2 ×3.14) ···(3) Irradiation time [s] = focal diameter [mm] / (scanning speed [m / min] × 1000 / 60) (4)
[0053] The stainless steel welded structure according to the embodiment of the present invention has a black color tone and good corrosion resistance and toughness of the weld metal, and is therefore used in various applications where such properties are required. Specifically, the stainless steel welded structure according to the embodiment of the present invention can be used as exhaust system parts such as mufflers, exterior and interior building panels, etc. EXAMPLES
[0054] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these.
[0055] Stainless steel having the composition shown in Table 1 (the balance being Fe and impurities) was melted and hot rolled to obtain a hot rolled sheet having a thickness of 3.0 mm, which was then annealed at 1050°C and pickled to obtain a hot rolled annealed sheet. Next, the hot rolled annealed sheet was cold rolled to obtain a cold rolled sheet having a thickness shown in Table 2 (sheet thickness T: 0.8 to 1.5 mm).
[0056] [Table 1]
[0057] Next, the cold-rolled sheet was heat-treated under the conditions shown in Table 2 to obtain stainless steel sheets. During the heat treatment, the O2 concentration and water vapor concentration were controlled to the specified values by adjusting the introduction ratio of O2 gas, N2 gas, and water vapor in the atmosphere furnace. Multiple test pieces measuring 300 mm (rolling direction) x 50 mm (width direction) were cut out from the obtained stainless steel sheet. The above test pieces were subjected to the following evaluations.
[0058] (Oxide film thickness) A 50 mm square measurement specimen was cut out from the test piece, and the surface was degreased with acetone. Next, analysis was performed using glow discharge optical emission spectroscopy (GD-OES) in accordance with JIS K0144:2018. In GD-OES, the thickness of the oxide film was defined as the depth from the surface to the position where O (oxygen) was 1 / 4 of the maximum value in the component concentration profile in the depth direction obtained. The element concentrations were calculated from the component concentration profile in the depth direction obtained by GD-OES.
[0059] (Carrier density of oxide film) A 20mm x 15mm test specimen was cut out from the test piece, a conductor was spot welded to one end, and the rest of the test surface (10mm x 10mm) was covered with silicone resin (one-liquid condensation type RTV rubber KE44 manufactured by Shin-Etsu Chemical Co., Ltd.). Next, a 0.1 mol / L Na2SO4 aqueous solution was used as the test liquid, and electrochemical impedance measurements were performed at 30°C in an Ar deaerated atmosphere. The electrochemical impedance measurements were performed using an electrochemical measurement system HZ-7000 manufactured by Hokuto Denko Co., Ltd., and a sine wave was applied at a predetermined potential to measure the impedance change, and the capacitance C of the oxide film was measured. The measurement potential was -0.2 to 0.5V vs. SSE (SSE indicates a saturated KCl silver-silver chloride electrode type reference electrode), sine wave 1Hz to 100kHz, and amplitude 10mV. Based on the obtained C, a 1 / C plot called a Mott-Schottky plot was performed. 2 In the graph of the -V curve, the slope A of the graph from 0 to -0.4 V was derived by the least squares method. The slope A and the carrier density N q is expressed by the following formula, and the carrier density of the oxide film was derived from the slope A based on this formula.
[0060]
number
[0061] In the above formula, N q is the carrier density, A is the slope of the Mott-Schottky plot, and e is the elementary charge (1.62×10 -19 C), ε is the relative dielectric constant of the oxide film (12), and ε0 is the dielectric constant of a vacuum (8.854×10 -12 F / m).
[0062] (color tone) The color tone of any five points on the test piece is measured using a spectrophotometer with a measurement diameter of 3 mm in accordance with JIS Z8722:2009, and the average value is calculated as CIELAB(L) in accordance with JIS Z8781-4:2013. * a * b * The lightness index L * , Chromathetics Index a * , b * As shown in.
[0063] The conditions for measuring the above color tone were as follows: Equipment: Konica Minolta CM-700d spectrophotometer Light source: Pulsed xenon lamp Photodetector: Dual 36-element silicon photodiode array Target mask: φ3mm Measurement: 10° field of view Auxiliary Illuminant: D65 daylight, color temperature 6504K Specular reflection processing mode: SCI
[0064] The above results are shown in Table 2. [Table 2]
[0065] For the two same type of test pieces obtained above, the rolling direction end faces were smoothed by cutting, and then the end faces were butted together and laser welded to obtain a stainless steel welded structure. The laser welding conditions are shown in Table 3. In Table 3, E / T represents the value of the irradiation energy E relative to the thickness of the stainless steel material (plate thickness T). [Table 3]
[0066] The obtained stainless steel welded structure was subjected to the following evaluations.
[0067] (area ratio of weld metal part) The periphery of the weld metal part of the stainless steel welded structure was photographed with an optical microscope. Next, a surface area of 20 mm in diameter centered on the weld metal part was observed, and the weld metal part was distinguished from the other parts (heat-affected zone and base metal) by binarization using the difference in brightness, and the area of the weld metal part was measured. The area of the weld metal part was then divided by the observation area (surface area of 20 mm in diameter) and multiplied by 100 to obtain the area ratio of the weld metal part to the surface area of 20 mm in diameter centered on the weld metal part.
[0068] (Oxide number density) The surface of the stainless steel welded structure was smoothed by wet polishing and then mirror polished. The amount of removal by these polishing processes was about 50 μm. Next, a FE-SEM (SU-5000, manufactured by Hitachi High-Tech Corporation) was used to remove about 0.7 mm from a 100 mm long welded metal part. 2 The oxides and inclusions were identified by image analysis. The composition of the oxides and inclusions was then analyzed by EDX to identify oxides with a major axis of 1 μm or more and to determine their number. The number of oxides with a major axis of 1 μm or more was then calculated based on the observation area (mm 2 ) to obtain the number density (pieces / mm 2 ) was sought.
[0069] (Corrosion resistance) The corrosion resistance was evaluated by a combined cycle corrosion (CCT) test. The CCT test was carried out as follows. First, a test piece for measurement, 50 mm wide x 100 mm long, was cut out from the stainless steel welded structure so that the weld metal part was located in the center and parallel to the length direction. Next, three sides of the test piece for measurement (except one side in the width direction) were covered with resin (one-liquid condensation type RTV rubber KE44 manufactured by Shin-Etsu Chemical Co., Ltd.). Next, two polyethylene tubes of 20 mmφ x 10 mm were bonded onto a Bakelite plate of 70 mm x 150 mm, and the side of the test piece for measurement that was not covered with resin and the opposite side were placed on top of the tubes and bonded. Next, the sample obtained in this way was placed in a CCT device so that the surface of the test piece for measurement was at 75° to the horizontal plane and the side of the test piece for measurement that was not covered with resin was at the bottom, and 10 cycles were performed, with 5% salt spray (35°C, 2 hours), drying (60°C, 25% RH, 4 hours), and wetting (50°C, 95% RH, 2 hours) as one cycle. The samples were then washed with water and dried, and the rust area ratio on the surface of the test specimens was evaluated (based on JIS Z2371:2015). In this evaluation, if the rating number (RN) was 8.0 or higher (corresponding to a rust area ratio of 0.25% or less), the corrosion resistance was judged to be good, and if the RN was less than 8.0, the corrosion resistance was judged to be poor.
[0070] (Toughness) The toughness was evaluated by bending as follows. First, a test specimen of 50 mm wide x 100 mm long was cut out from the stainless steel welded structure so that the weld metal part was located at the center and parallel to the length direction. Next, a universal testing machine was used to perform 1T bending so that the longitudinal direction of the weld metal part was perpendicular to the bending ridge line. The 1T bending process is a process in which the test specimen is bent 180° with a plate of the same thickness as the test specimen sandwiched inside the bending direction of the test specimen. In this bending process, the test specimens that did not crack in the weld metal part were judged as ○ (good toughness), and the test specimens that cracked in the weld metal part were judged as × (poor toughness).
[0071] The above results are shown in Table 4. [Table 4]
[0072] As shown in Table 4, the stainless steel welded structures of Examples 1 to 5 used stainless steel materials having a specified composition on which an oxide film having a specified thickness and carrier density was formed, and had weld metal parts in which the area ratio and number density of the oxide in a surface area with a diameter of 20 mm were within specified ranges. Therefore, the weld metal parts had a black color tone and good corrosion resistance and toughness.
[0073] In contrast, the stainless steel welded structures of Comparative Examples 1 and 2 were made of stainless steel with a high carrier density of the oxide film, and therefore the corrosion resistance of the weld metal parts was insufficient. The stainless steel welded structure of Comparative Example 3 had good corrosion resistance and toughness of the weld metal part, but was unable to ensure a black color tone. In the stainless steel welded structure of Comparative Example 4, the value of irradiation energy relative to the thickness of the stainless steel material during laser welding (E / T) was too high, so the area ratio of the welded metal part increased and the corrosion resistance of the welded metal part decreased. In the stainless steel welded structure of Comparative Example 5, the value of the irradiation energy relative to the thickness of the stainless steel material during laser welding (E / T) was too low, so the number density of oxides in the weld metal joint increased and the toughness of the weld metal joint decreased. The stainless steel welded structure of Comparative Example 6 was made of stainless steel with a low Cr content and a high carrier density of the oxide film, and therefore the corrosion resistance of the weld metal was insufficient. The stainless steel welded structure of Comparative Example 7 had good corrosion resistance and toughness of the weld metal part, but the black color tone could not be ensured due to the low Mn content.
[0074] As can be seen from the above results, the present invention can provide a stainless steel welded structure which has a black color tone and excellent corrosion resistance and toughness of the weld metal part, and a method for manufacturing the same. [Explanation of symbols]
[0075] 10 Base material 11 Materials Department 12 Oxide film 20 Heat-affected zone 30 Welded metal parts 100 Stainless steel welded structure
Claims
1. A stainless steel welded structure having a base material and a weld metal part, The base material is a stainless steel material having a material portion and an oxide film formed on the material portion, the material portion has a composition including, by mass, C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities; The oxide film has a thickness of 300 to 1000 nm and a carrier density of 2.0×10 20 pieces / cm 3 is as follows: The weld metal part has a density of oxide particles having a major axis of 1 μm or more of 5 particles / mm 2 is as follows: A stainless steel welded structure, wherein the area ratio of the weld metal portion to a surface area having a diameter of 20 mm centered on the weld metal portion is 20.0% or less.
2. The stainless steel welded structure according to claim 1, wherein the material portion further contains, by mass, at least one selected from Nb: 0.50% or less, Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
3. The oxide film of the base material is L * a * b * Lightness index L in color system * is 50.0 or less, Chromathetics Index a * and b * The stainless steel welded structure according to claim 1 or 2, wherein the value of is within ±5.
00.
4. The present invention has a material part and an oxide film formed on the material part, the material part containing, by mass, C: 0.100% or less, Si: 1.00% or less, Mn: 0.05 to 1.00%, Ni: 1.00% or less, P: 0.100% or less, S: 0.100% or less, Cr: 16.00 to 25.00%, N: 0.100% or less, Ti: 0.08 to 0.50%, Cu: 1.00% or less, and Mo: 2.00% or less, with the balance being Fe and impurities, and the oxide film has a thickness of 300 to 1000 nm and a carrier density of 2.0×10 20 pieces / cm 3 A method for manufacturing a stainless steel welded structure by laser welding stainless steel materials that are as follows: Laser welding is performed by applying irradiation energy [kJ / mm] to the thickness [mm] of the stainless steel material. 2 ] is 10.0 to 30.0 kJ / mm.
5. 5. The method for manufacturing a stainless steel welded structure according to claim 4, wherein the material portion further contains, by mass, at least one selected from Nb: 0.50% or less, Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, Sn: 0.100% or less, and B: 0.0100% or less.
Citation Information
Patent Citations
Production of black-colored ferritic stainless steel
JP1998330904A
Black stainless steel plate and its production
JP1999061376A
Black ferritic stainless steel sheet
JP2018135591A
Black stainless steel sheet and method for manufacturing the same
JP2019178392A
Ferritic stainless steel material
JP2022103732A